Effect of the Dynamic Lactate Style to Developing Defensive and Offensive Performance Endurance for Handball Players Under 19 Years - Zahra Ali Hassan; Hussein Mnaty Sachit (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in the application of a modern training method for training handball inorder to raise the player’s physiological and skill efficiency throughout the game and maintain a constantlevel of performance and resistance to fatigue, especially the ability to perform with the presence of lacticacid and benefit from it after converting it to energy. The research aims: To identify the effect of the dynamiclactate method on developing the tolerance for defensive and offensive performance of handball playersunder 19 years of age. The researchers used the experimental design with two groups of experimental andcontrol, with pre and post- test, for its suitability to the nature of the problem. The researcher identifiedthe research community with handball players in the Karbala Sports Club for the youth category of under19 years of age for the 2020-2021 training season, whose number is (16) players. By (7) players for eachgroup. As for the most important conclusions, the results of this study demonstrated the effectiveness of thedynamic lactate method in developing endurance of defensive and offensive performance with handballamong the players of the research sample, while the recommendations were, the researchers recommendedthat the dynamic lactate method should be used in the training units..